Evaluation of Antifibrotic Mechanisms of 3′5-Dimaleamylbenzoic Acid on Idiopathic Pulmonary Fibrosis: A Network Pharmacology and Molecular Docking Analysis - Karina González-García; Jovito Cesar Santos-Álvarez; Juan Manuel Velázquez-Enríquez; Cecilia Zertuche-Martínez; Edilburga Reyes-Jiménez; Rafael Baltiérrez-Hoyos; Verónica Rocío Vásquez-Garzón (Drugs and Drug Candidates)
Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, disabling disorder of unknown etiology, poor prognosis, and limited therapeutic options. Previously, 3′5-dimaleamylbenzoic acid (3′5-DMBA) was shown to exert resolving effects in IPF, offering a promising alternative for treating this disease; however, the molecular mechanisms associated with this effect have not been explored. Objetive: We evaluated the potential antifibrotic mechanisms of 3′5-DMBA by network pharmacology (NP) and molecular docking (MD). Methods: 3′5-DMBA-associated targets were identified by screening in SwissTargetPrediction. IPF-associated targets were identified using lung tissue meta-analysis and public databases. Common targets were identified, and a protein–protein interaction (PPI) network was constructed; we ranked the proteins in the PPI network by topological analysis. MD validated the binding of 3′5-DMBA to the main therapeutic targets. Results: A total of 57 common targets were identified between 3′5-DMBA and IPF; caspase 8, 9, 3, and 7; myeloid leukemia-induced cell differentiation protein Mcl-1; and poly [ADP-ribose] polymerase 1 are primary targets regulating PPI networks. Functional analysis revealed that the common targets are involved in the pathological features of tissue fibrosis and primarily in the apoptotic process. MD revealed favorable interaction energies among the three main targets regulating PPI networks. Conclusions: NP results suggest that the antifibrotic effect of 3′5-DMBA is due to its regulation of the pathological features of IPF, mainly by modulating signaling pathways leading to apoptosis, suggesting its therapeutic potential to treat this disease.